Behind the slow start: An assessment of early childhood care and development in the Philippines - Valerie Gilbert Ulep; Lyle Casas; Aaron Carlos G. Manuel; John Paulo D. Mendoza; Joy Bagas; Kim Leonard G. Dela Luna (Philippine Institute for Development Studies (PIDS), 2024)
This report assesses the Early Childhood Care and Development (ECCD) in the Philippines, aiming to support the Second Congressional Commission on Education (EDCOM2) of the Philippine Congress with empirical evidence for programmatic and legislative reforms. Our assessment uses a comprehensive framework that analyzes the health, nutrition, and early education outcomes of Filipino children and examines their access to essential health, nutrition, and early education services. We analyze demand- and supply-side inputs such as governance, financing, infrastructure, and human resources to identify factors that explain the poor and inequitable access to these basic services. Throughout our analysis, we highlight key principles for optimizing ECCD returns: (1) timely provision of crucial interventions during critical life stages, (2) ensuring comprehensive access to essential services, and (3) upholding quality standards with far-reaching impacts on health, nutrition, and education outcomes.
Keywords: 330; early childhood care and development (ECCD); early education; health and nutrition; Philippines